Simultaneous quantitative analysis of polyphenolic compounds in human plasma by liquid chromatography tandem mass spectrometry. Issue 18 (8th August 2019) - Shafaei, Armaghan; Croft, Kevin; Hodgson, Jonathan; Boyce, Mary C.
Abstract: A diet rich in polyphenolic compounds has recognized health benefits, and as such is routinely monitored as part of dietary intervention studies. A method for the simultaneous determination of 36 phenolic compounds, including phenolic acids and flavonoids, using liquid chromatography and tandem mass spectrometry is described here. The target analytes were quantified based on their specific mass spectral fragments using a selected reaction monitoring approach. A C18 column with embedded aromatic functionality ensured separation of all phenolic compounds studied which included several pairs of isomers. Sample preparation involved the use of β‐glucuronidase to release the phenolic compounds from their conjugated forms. The intra‐day and inter‐day precision and accuracy was less than 7% for all phenolic compounds studied. Recoveries, where plasma was spiked with three different concentrations of the analytes, ranged from 95–115%. The limits of detection and quantification were 0.23–3.89 and 1.15–7.79 nM, respectively. The method was successfully applied to real samples and the range reported for each phenolic compound, with the exception of hydroferulic acid, nordihydroguaiaretic acid, methylgallate, and m ‐coumaric acid, was at least an order of magnitude higher than the limit of quantification for the method.